PENGARUH PERCEIVED SERVICE TERHADAP CITRA MUSEUM NEGERI JAMBI - DINI ELIDA PUTRI (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2016)
The Museum Jambi Province is one of the places that collect, research, and display the collection of Jambi’s heritage. The Museum Jambi Province, which is categorized as a public sector in part of Ministry Culture and Tourism of Jambi Province, was expected to have the image of as an edutainment recreational site while delivering its historical values. The objective of this research is to describe the effect of five dimension of the service quality (reliability, responsiveness, assurance, empathy, and tangible) perceived by the visitors to the image of Museum Jambi Province. Population of this research is the student of senior high school that had been the visitors of Museum Jambi Province. The amount of 275 students as the research sample was chosen with Probability Sampling Technique. Based on the conducted research, the five dimension of the service quality simultaneously have a significant but yet not a strong effect to the image of Museum Jambi Province, approximately 48,3 percent. Empathy and Tangibles are the two dimensions that significantly have an effect to the Image of Museum Jambi Province (approximately 0,241 and 0,382), with the most attention should be aimed at attribute of delivering the right service for the right visitors and the modern technology supporting the service of Museum Jambi Province.